Antenna Sensitivity Enhancement through Noise Suppression in an LTE/GPS Communication Module - Jeonghwan Kim; Seokju Wi; Hoseung Lee; Rui Li; Hyunwoong Shin; Hyung-Hoon Kim; Hyeongdong Kim (Journal of Electromagnetic Engineering and Science)
This letter discusses antenna sensitivity enhancement in an LTE/GPS communication module for vehicle-to-everything applications by addressing onboard noise suppression. The performance of antennas in smart vehicles is increasingly complex due to the concentration of electronic devices within small structures, which impacts signal reception. Onboard noise generated by other unknown electronic components on the PCB can couple through the resonance structure of the other antenna, significantly degrading performance. The proposed solution includes an equivalent noise circuit and two double-branch planar inverted-F antennas targeting the B1 and B5 LTE bands and the L1 and L5 GPS bands. The noise circuit can couple with the GPS antenna’s feed loop and requires a noise suppression method to prevent sensitivity degradation. The analysis shows that this approach can increase total isotropic sensitivity from −81.79 dB to −94.61 dB, representing a significant enhancement in antenna sensitivity performance.